A Fragment of the Acta Pauli in the Michigan Collection - Sanders, Henry A. (Harvard theological review, 1938)
The fragment, P. Mich. 1317, is a damaged scrap of papyrus 19.8 by 6.3 cm. (7¾ by 2½ inches). It is much darkened with age and otherwise damaged by dirt, water, and wear. It is a portion of a leaf of a book written on both sides, which came into our collection classified as a bit of a lost Gospel, though it did not seem to me to conform to that designation. My first transcript of the text was shown to my colleague Professor Bonner, and by him to Dr. H. I. Bell of the British Museum and to Sir Frederic Kenyon. All agreed that these fragmentary remnants seem to have belonged to a homily. A transcript of the text was also sent to Professor Kirsopp Lake for suggestions on the probable authorship. Upon the publication of the Acta Pauli by Schmidt and Schubart he at once notified me of the identity in text and we both immediately thereafter established that the Michigan and Berlin fragments were parts of a single leaf. A page number, πc (= 86), is found just above the beginning of the first line on the side, where the outer margin is preserved. A similar page number on the opposite side of the leaf must have perished, as there only the ends of the lines are preserved. It is the part of the leaf next to the binding that is lost.